A clinico-hematological study of severe anemia in hospitalized children aged 6 months to 12 years in a tertiary care institute from North India: An observational study - Savita Gour; Mukesh Vir Singh; Vatsala Misra; Anubha Shrivastava; Nandita Mishra; Shahid Akhtar Siddiqui (Al Ameen Journal of Medical Sciences, 2025)
Background: Anemia is a global health problem, more so in low- and middle-income countries (LMIC) like India. Prevalence of anemia in children is rising in recent years, as reflected by National Family Health Survey - 5 data (2019-21), despite many government programs for its prevention. If not diagnosed and treated timely, these children may land up into severe anemia, which frequently requires blood transfusion. Purpose: To understand severe anemia in children, in a better way, which may be helpful in chalking out preventive and therapeutic strategies. Methods: Hospitalized children aged 6 months to 12years, having severe pallor on clinical examination were included. Apart from history taking and clinical examination, complete blood counts (including hemoglobin) along with other relevant investigations were done on venous blood. Severe anemia was defined as Hb < 7 g/dl in children aged 6-59 months and Hb < 8 g/dl in children aged 5-12 years as per WHO criteria. Result: Commonest age group of severe anemia children was 6 months-2years. Risk factors included low birth weight, younger age, lower socioeconomic status, improper feeding practices with lesser consumption of iron rich food and malnutrition. Majority presented with symptoms of respiratory tract infection and elevated body temperature at the time of admission. Maximum cases had microcytic hypochromic anemia. Iron deficiency anemia was found to be the commonest cause of severe anemia in 45% cases. Severe acute malnutrition is associated with a relatively lower level of hemoglobin of <5 gm/dl. Conclusion: Severe anemia is more common in under 5-year children. Early diagnosis of severe anemia with clinical and basal blood parameters, along with its etiology is essential before start of treatment, to avoid unwanted side effects e.g., iron overload. Anemia is frequently associated with malnutrition, so there is a need for parental counselling for child feeding practices, apart from ongoing deworming and iron-folic acid supplementation programs by the government.